Comparative efficacy of various exercise interventions on sleep in patients with cognitive impairment: a systematic review and meta-analysis - Zhang, Junlei; Liu, Yan; Sun, Qingling; Shi, Jing; Ni, Jingnian; Li, Ting; Long, Ziyi; Wei, Mingqing; Tian, Jinzhou (Frontiers in Neurology, 2024)
Background Sleep disturbances are an early indicator of cognitive impairment and exacerbate its progression. While pharmacological treatments for sleep disorders exist, their side-effect profile includes an increased risk of falls and the potential to exacerbate cognitive impairment. Non-pharmacological treatments such as physical exercise should be considered. However, uncertainties persist. We aimed to assess the potential benefits of exercise interventions on sleep in patients with cognitive impairment and determine the specific effects of various exercise modalities. Materials and methods A systematic search was performed on seven databases for eligible studies published before Nov 2022. Randomized controlled trials of exercise for patients with cognitive impairment (mild cognitive impairment and Alzheimer’s disease) were included. All analyses were conducted using RevMan version 5.4. Meta-analysis and The Grading of Recommendations Assessment Development and Evaluations (GRADE) quality ratings were performed on sleep quality and objective sleep data. Results A total of 8 randomized controlled trials were included with a sample size of 486 subjects. For patients with cognitive impairment, physical exercise had a beneficial effect on sleep quality [MD = −3.55 (−5.57, −1.32), Z = 3.13, p = 0.002] and total sleep time [MD = 33.77 (23.92, 43.62), Z = 6.72, P < 0.00001]. No improvement was found in sleep efficiency and nocturnal awakening time. Subgroup analysis showed that multi-component exercise produced superior results. Conclusion Physical exercise may improve sleep quality and total sleep time for patients with cognitive impairment. Multi-component exercise designed individually is more effective. Large-scale randomized controlled trials with objective sleep outcome measurements are warranted. Clinical trial registration: https://www.crd.york.ac.uk/prospero/, identifier: CRD42022377221.